STATUS OF DISABILITY IN INDIA - 2007 Vol.1 - Hearing Impairment & Deaf Blindness - Rathna N (Journal of All India Institute of Speech and Hearing, 2009)
Book Review on ‘Status   of Disability  in  India  –  2000,  2003  and  2007’.  The latest book ‘STATUS  OF DISABILITY  IN INDIA –2007’ was published in the year 2008.